Selection of Potential Lignin-Degrading Bacteria and Fungi Isolates from the Gunung Lumut and Sungai Wain in East Kalimantan - Ruhimat, Riki; Kumala Dewi, Tirta; Noviana, Zahra; Sutisna, Entis; Mulyani, Nani; Juwari, Micha; Sufaati, Supeni; Antonius, Sarjiya; Verchius, Eric (Biosaintifika: Journal of Biology & Biology Education, 2025)
The enzymes laccase (Lac), manganese peroxidase (MnP), and lignin peroxidase (LiP) are ligninolytic enzyme groups that have a crucial role in degrading lignin compounds. These complex components are abundant in plant biomass. This research aims to isolate and characterize microorganisms producing the enzymes Lac, MnP, and LiP from leaf litter, rhizosphere soil, and sediment in the Gunung Lumut Protected Forest (GLPF) and Sungai Wain Protected Forest (SWPF), East Kalimantan. The bacterial and fungal isolates obtained were cultured on NA and PDA media enriched with 0.05% guaiacol as a substrate. Initial selection was carried out based on the colony growth rate and the formation of a brownish discoloration zone, which indicates ligninolytic enzyme activity. The superior isolates were then tested for extracellular enzyme activity quantitatively using a UV-Vis spectrophotometer. Among the bacterial isolates, the highest Lac activity is isolated GLS 5.1.2 (173.44 U L-1); the highest MnP activity is isolated GLS 5.3 (177.41 U L-1); and the highest LiP activity is isolated GLS 5.1.2 (1034.05 U L-1). In the group of fungi, isolate SS2 was detected with the highest Lac activity (20.66 U L-1), MnP activity (333.75 U L-1), and LiP activity (2516.13 U L-1). Biodiversity sources in the Gunung Lumut Protected Forest (GLPF) and Sungai Wain Protected Forest (SWPF), East Kalimantan have the potential to produce microbial isolates with unique enzymatic characteristics that have never been reported before. The resulting microbial isolate can be used as a bioactivator in composting organic waste to produce high-quality organic fertilizer.